Danshensu Ethyl Ester Alleviates LPS-Induced Acute Lung Injury by Targeting the NLRP3 Inflammasome - Ding W; Xu S; Xie S; Dong Y; Jiang Y; Xie N; Wang P; Feng J; Qu G (Journal of Inflammation Research)
Wensi Ding,1,2,* Sen Xu,1,* Shuyang Xie,1,3,* Yao Dong,4 Yujie Jiang,4 Ning Xie,5 Pingyu Wang,6 Jiankai Feng,2 Guiwu Qu7 1Department of Biochemistry and Molecular Biology, Binzhou Medical University, Yantai, People’s Republic of China; 2Department of Laboratory Medicine, Yantai Affiliated Hospital of Binzhou Medical University, Yantai, People’s Republic of China; 3Shandong Laboratory of Advanced Materials and Green Manufacturing, Yantai, People’s Republic of China; 4Binzhou Medical University, Yantai, People’s Republic of China; 5Yantaishan Hospital, Yantai, People’s Republic of China; 6Department of Epidemiology, Binzhou Medical University, YanTai, People’s Republic of China; 7Department of Traditional Chinese Medicine, School of Pharmacy, Binzhou Medical University, Yantai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiankai Feng, Department of Laboratory Medicine, Yantai Affiliated Hospital of Binzhou Medical University, No. 717, Jinbu Avenue, Yantai, 264100, People’s Republic of China, Email Fengjiankai@bzmc.edu.cn Guiwu Qu, Department of Traditional Chinese Medicine, School of Pharmacy, Binzhou Medical University, No. 346, Guanhai Road, Yantai, 264003, People’s Republic of China, Email qu_guiwu@bzmc.edu.cnPurpose: To investigate whether Danshensu ethyl ester (DEE) can attenuate acute lung injury (ALI) and explore the detailed mechanism.Methods: The ALI model was induced in mice using LPS. The effects of DEE on lung wet-to-dry weight ratio (W/D), bronchoalveolar lavage fluid (BALF) protein levels, and neutrophil infiltration (neutrophils) were assessed. In addition, molecular docking and molecular dynamics simulations were also carried out to determine the binding situation between DEE and NLRP3. We evaluated in both in vivo and in vitro models the expression of NLRP3-related proteins as well as the release of cytokines. The generation of reactive oxygen species (ROS) and the formation of ASC fluorescent specks in cells were also observed.Results: The results demonstrated that DEE significantly alleviated pulmonary edema and lung injury of mice. Molecular docking and simulations revealed that DEE directly targets and tightly binds to the NLRP3 protein. Furthermore, both in vivo and in vitro experiments showed that DEE suppressed activation of the NF-κB signaling pathway induced by LPS, and decreased the expression of NLRP3, ASC, and cleaved caspase-1, inhibiting the release of cytokines such as IL-1β, IL-6, and TNF-α. Additionally, DEE suppressed ROS generation and ASC specks formation, thereby inhibiting the assembly and activation of the NLRP3 inflammasome.Conclusion: DEE exerts an inhibitory influence on the LPS-induced inflammatory response by suppressing the activation of the NLRP3 inflammasome. This study provides the potential application of DEE in NLRP3-driven ALI therapy. Keywords: acute lung injury ALI, danshensu ethyl ester DEE, lipopolysaccharide LPS, NLRP3 inflammasome, inflammation, neutrophil